Visual Trespassings: Explorations of the Limit in Contemporary American Visual Arts: Sally Mann’s Dead Bodies - Botescu Sireteanu, Ileana (University of the West, 2022)
Drawing on cultural studies, visual culture and semiotics, the present study investigates the particular ways in which contemporary visual arts approach the ontological issue of the limit, in a culture that has gradually and persistently blurred all limits to near erasure. In this sense, this study looks at American photographer Sally Mann's visual explorations of the body-as-flesh, as bold interrogations of cultural taboos, as well as innovative visual cues of ontological and epistemological transgression and inquiry.
Keywords: body; death; limit; representation; visual culture